PENERAPAN SMS GATEWAY DALAM MEMBERIKAN PERUBAHAN HARGA SAWIT DI KUD ANUGERAH BAGAN BATU - Sihombing, Volvo; Siahaan, Nimrot; Panjaitan, Bernat (Jurnal Mantik Penusa, 2020)
The existence of the Agricultural Research Agency for 30 years has been quite successful in procuring agricultural innovations. Several innovations (technology, institutions and policies) have been widely used and proven to be the main triggers for the growth and development of businesses and agribusiness systems. In this case KUD Anugerah cooperates with the palm oil mills (VFD) exchange of information on palm prices which is always updated so that the public knows the development of oil prices in the KUD. The KUD will supply palm oil at the lowest price pksKeywords: sms, gateway, kud, palm.